Intravenous Colistin Use for Multidrug-Resistant Gram-Negative Infections in Pediatric Patients - (:unkn) unknown (My University, 2016)
0

Background: The emergence of infections due to multidrug-resistant Gram-negative bacilli (MDRGNB) has led to the resurrection of colistin use. The data on colistin use and drug-related adverse effects in children are scarce. Aims: In this study, we aimed to evaluate the clinical efficacy and safety of colistin use in critically ill pediatric patients. Study Design: This study has a retrospective study design. Methods: Sixty-one critically ill children were identified through the department's patient files archive during the period from January 2011 to November 2014. Results: Twenty-nine females and thirty-two males with a mean±standard deviation (SD) age of 61±9 months (range 0-216, median 12 months) received IV colistin due to MDR-GNB infections. Bacteremia (n=23, 37.7%) was the leading diagnosis, followed by pneumonia (n=19, 31%), clinical sepsis (n=7, 11.4%), wound infection (n=6, 9.8%), urinary tract infection (n=5, 8.1%) and meningitis (n=1, 1.6%). All of the isolates were resistant to carbapenems; however, all were susceptible to colistin. The isolated microorganisms in decreasing order of frequency were: Acinetobacter baumanni (n=27, 44.2%), Pseudomonas aeruginosa (n=17, 27.8%), Klebsiella pneumoniae (n=6, 9.8%), K. pneumoniae and Stenotrophomonas maltophilia (n=1, 1.6%), K. pneumoniae and A. baumanni (n=1, 1.6%), K. oxytoca (n=1, 1.6%) and Enterobacter cloacae (n=1, 1.6%). In seven patients, no microorganisms were detected; however, five of these patients were colonized by carbapenem-resistant K. pneumoniae. The mean duration of colistin therapy was 12 days (range 3-45). Colistin was administered concomitantly with one of the following antibiotics: carbapenem (n=50, %82), ampicillin-sulbactam (n=5, 8%), quinolones (n=5, 8%), rifampicin (n=1, 1.6%). Carbapenem was the most frequently used antibiotic. Nephrotoxicity was observed in only 1 patient, and we did not observe neurotoxicity in this study. All the patients received intravenous colistin (colisthimethate) at a dosage of 5 mg/kg daily by dividing it in three equal doses. Seven (11.4%) patients died during the study period. Conclusion: Colistin appears to be a safe and efficacious drug for treating MDR-GNB infections in children.
Keywords: Cerrahi